Psychotropic drugs for the management of cancer‐related fatigue: a systematic review and meta‐analysis. (21st October 2015) - Qu, D.; Zhang, Z.; Yu, X.; Zhao, J.; Qiu, F.; Huang, J.
Abstract : Cancer‐related fatigue (CRF) is a common symptom affecting 60–90% of cancer survivors, and effective management for CRF is not yet available. Recently, an increasing number of trials examining the use of psychotropic drugs for the treatment of CRF have been performed, but these trials have yielded inconsistent results. Therefore, we conducted a meta‐analysis aimed at assessing the effect and safety of psychotropic drugs for the management of CRF. Ten eligible trials of the psychotropic drugs methylphenidate and modafinil in a total of 1582 participants treated for CRF were subjected to statistical analyses. A meta‐analysis of seven of these studies indicated that methylphenidate was superior to placebo for the treatment of CRF. Another meta‐analysis of three studies evaluating modafinil found that this drug was no better than placebo. Adverse events were similar between both methylphenidate and modafinil and the placebo groups. Our meta‐analysis indicated that the treatment of CRF with methylphenidate appears to be effective, whereas modafinil provides no benefit. These results of this analysis warrant further trials to confirm the efficacy and safety of psychotropic drugs for the treatment of CRF.